2021
DOI: 10.4103/jfmpc.jfmpc_674_21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological determinants of leptospirosis in rural and urban districts of Maharashtra, India

Abstract: Background: Leptospirosis is emerging as one of the growing public health problems in many parts of India. It can occur in both rural and urban areas with varied risk factors. This study was taken up in three districts of Maharashtra namely—Mumbai, Ratnagiri, and Sindhudurg to understand the determinants of leptospirosis in both the urban and rural areas and look for differences if any. Materials and Methods: This cross-sectional study was carried out during the year 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
2
2
1
Order By: Relevance
“…In our study, majority of the patients belonged to the age group of 18-45 years indicating potential risk of occupational exposure among these working age group which is in concurrence with study findings by Patil DY[ 20 ] in Mumbai, wherein the majority of cases were in the age group of 25-50 years and studies done in northern and coastal part of India[ 21 - 23 ] and also in different parts of the world. [ 18 , 19 ] The gender-wise distribution of cases was almost equal in our study which is contrast to studies by Holla R et al ,[ 21 ] Kembhavi RS,[ 24 ] and by DebMandal M[ 25 ] reported prevalence was high among males. This might be due to factors like migration of male working population for better employment opportunities and female member of the family looking after the agricultural activities.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, majority of the patients belonged to the age group of 18-45 years indicating potential risk of occupational exposure among these working age group which is in concurrence with study findings by Patil DY[ 20 ] in Mumbai, wherein the majority of cases were in the age group of 25-50 years and studies done in northern and coastal part of India[ 21 - 23 ] and also in different parts of the world. [ 18 , 19 ] The gender-wise distribution of cases was almost equal in our study which is contrast to studies by Holla R et al ,[ 21 ] Kembhavi RS,[ 24 ] and by DebMandal M[ 25 ] reported prevalence was high among males. This might be due to factors like migration of male working population for better employment opportunities and female member of the family looking after the agricultural activities.…”
Section: Discussioncontrasting
confidence: 99%
“…This temporal association could be due to animal and poultry waste which attracts rodents resulting in frequent transmission of the disease through contamination of soil with urine. These findings are in line with studies done in Maharashtra,[ 24 ] Middle Andaman,[ 27 ] and by Regmi L,[ 18 ] Esfandiari B et al ,[ 29 ] Suwanpakdee S,[ 34 ] and by Mwachui MA. [ 35 ] Our study also noted that rodent exposure factors like presence of rodents in the house and at the workplace and also presence of grain storage areas like godown had a higher risk for leptospirosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies in Puerto Rico [ 59 ], Thailand [ 52 ], and Nicaragua [ 38 ] did not find evidence that rash was an indicator of severe or fatal leptospirosis. In India, one study found that skin rash was significantly associated with leptospirosis in children [ 60 ], and another study found only suggestive evidence of such an association among urban leptospirosis cases [ 61 ], but not a sign of severity. However, previous evidence in Colombia suggested that rash is more common in other infections and may even be used, for example, to differentiate between dengue and leptospirosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that leptospirosis is re-emerging, and it is becoming a public health problem, worldwide, with significant increases in its incidence and there being multiple outbreaks [176]. Recently, the disease has become widespread in Nicaragua, Brazil, India, Southeast Asia, the United States, and in several other countries [177][178][179][180][181][182][183][184]. Despite this, there are a few reports of leptospirosis in South and Southeast Asia, especially in the densely populated countries such as India and Indonesia, because the monitoring of it is very poor [171].…”
Section: Leptospirosismentioning
confidence: 99%